APPLICATION OF DRILL METHOD (EX/ERCISE) ON LEARNING MATERIALS OF ENGINEERING TECHNIQUE IN CLASS X ENGINEERING SMALL ENGINEERING (TKR) SMK NEGERI 1 PALANGKA RAYA 2016/2017 - Gigih Susanto; Sanggam R.I Manalu (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2017)
The Drill (Exercise), Results Learning, Image Technique are the topic of study aiming to determine how the learning outcomes of students after doing the learning method Drill (Exercise) in class X Light Vehicle Engineering SMK 1 of Palangkaraya in Academic Year 2016/2017. The population for this study is the class X Light Vehicle Engineering SMK Negeri 1 Palangkaraya totaling 42 students. The collection of data is done using the test, which is in the form of the posttest and observation sheet consisting of student activity sheet, and the student’s questionnaire responses. Date were collected and then analyzed by using the average value of the posttest. Based on the results of data analysis posttest average value of 81.71, all and KKM students exceeds the value set by the school. From this research we can conclude student learning outcomes can be better if you use the learning method Drill (Exercise).